Sublingual Gland and Mylohyoid Muscle Advancement: A Novel Combined Local Soft Tissue Reconstruction. Issue 2 (28th March 2021) - Benech, Rodolfo; Bowen, Luke; Handley, Thomas
Abstract : Abstract: Here the authors present the surgical management of a 78-year-old female with a superficial squamous cell carcinoma of the mucosa overlying her edentulous mandibular alveolus with no evidence of bony invasion. Combining the superficial nature of the lesion, patient age and substantial medical comorbidities, a limited intra-oral resection was planned, to avoid the need for free flap reconstruction. The operation required a wide local excision with clear clinical margins and a mandibular rim resection. All of the currently available reconstructions would result in prolonged surgical time, donor site morbidity, and possible secondary procedures. To overcome these pitfalls, a sublingual gland and mylohyoid muscle advancement flap was designed and executed. By combining the mylohyoid muscle and sublingual gland tissue as an advancement flap in a tension-free manner, secured to the remaining circumferential mucosa, a watertight closure was achieved. After an uneventful recovery without complication the patient was discharged the following day. Complete epithelialization was observed on day 25. Adjuvant radiotherapy was offered to reduce the risk of recurrence and progression. To date, no bony exposure and no pathological fractures have occurred. In conclusion, the entire procedure is simple and innovative. There is minimal donor site morbidity, with an immediate return to oral diet and tolerable surgical risks. It requires a small amount of surgical time compared to other reconstructive options and an overall reduced inpatient stay.